The impact of rainfall shocks on child mortality - Rosario, Loretta May Y. (School of Economics, University of the Philippines Diliman, 2019)
The Philippines is vulnerable to extreme weather events and natural disasters due to its geographical location and physical environment. Given the country_s volatility to weather shocks, we find it vital to examine their possible impact on children, one of the most vulnerable members of society. The main purpose of this paper is to determine if rainfall shocks have a significant impact on child mortality in the Philippines. We used the rainfall data from the Philippine Atmospheric, Geophysical, and Astronomical Services Administration (PAGASA) and the health data from the National Demographic and Health Survey (NDHS). Using multiple logistic regression, we find that rainfall shock experienced in utero (t minus 1) has a statistically significant and positive impact on child mortality in agricultural regions. This implies an adverse effect where the higher the rainfall shocks, the higher the chances that the child is going to die. We also used the Cox Regression Proportional Hazards Regression analysis and the Weibull Accelerated Failure Time Model which showed consistent results where rainfall shocks experienced at the child_s early stages of life, specifically at periods (t plus 2), (t plus 3), and (t plus 4), have a statistically significant impact on child mortality. Our results show that as rainfall shock increases, the hazard rate increases and the survival time of the child decreases, respectively. Furthermore, we also find it interesting that the mother_s educational background appears to be a significant variable affecting the survivability of the child, which implies that the child is less likely to die if the mother has a higher level of education. Our paper particularly contributes to the limited literature regarding the impact of climatic or weather shocks on child health in the Philippines.